First evidence for cold-adapted anaerobic oxidation of methane in deep sediments of thermokarst lakes - Winkel, M.; Sepulveda-Jauregui, A.; Martinez-Cruz, K.; Heslop, J. K.; Rijkers, R.; Horn, F.; Liebner, S.; Anthony, K. M. Walter (My University, 2019)
Microbial decomposition of thawed permafrost carbon in thermokarst lakes leads to the release of ancient carbon as the greenhouse gas methane (CH4), yet potential mitigating processes are not understood. Here, we report delta C-13-CH(4)signatures in the pore water of a thermokarst lake sediment core that points towardsin situoccurrence of anaerobic oxidation of methane (AOM). Analysis of the microbial communities showed a natural enrichment in CH4-oxidizing archaeal communities that occur in sediment horizons at temperatures near 0 degrees C. These archaea also showed high rates of AOM in laboratory incubations. Calculation of the stable isotopes suggests that 41 to 83% ofin situdissolved CH(4)is consumed anaerobically. Quantification of functional genes (mcrA) for anaerobic methanotrophic communities revealed up to 6.7 0.7 x 10(5)copy numbers g(-1)wet weight and showed similar abundances to bacterial 16S rRNA gene sequences in the sediment layers with the highest AOM rates. We conclude that these AOM communities are fueled by CH(4)produced from permafrost organic matter degradation in the underlying sediments that represent the radially expanding permafrost thaw front beneath the lake. If these communities are widespread in thermokarst environments, they could have a major mitigating effect on the global CH(4)emissions.
Keywords: permafrost; anme-2d; subsurface; c-13-methane; methanoperedenaceae